PSYCHOLINGUISTIC ASPECT OF ENGLISH LANGUAGE TEACHING IN ELEMENTARY GRADES - Norkobilov , Murod G‘ayrat O‘g‘li (Educational Research in Universal Sciences, 2023)
Psycholinguistics is a separate branch of science that studies human speech. The psycholinguistic aspect of the methodology studies the specific features of speech development of elementary school students in the process of learning English. Unlike the sociolinguistic aspect, which methodically organizes language material according to the educational content, the psycholinguistic aspect is of particular importance for the modern English language teacher. Because in this area, it helps to understand the specific features of the modern student in learning English, the stages and dynamics of speech activity development. A teacher who is aware of these features will be able to understand issues related to the interrelationship of language, speech and speech activity.